2011
DOI: 10.1128/jvi.02344-10
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus Gene UL79 Is Required for the Accumulation of Late Viral Transcripts

Abstract: In this study, we adopted a conditional protein genetic approach to characterize the role of the human cytomegalovirus (HCMV) gene UL79 during virus infection. We constructed ADddUL79, a recombinant HCMV in which the annotated UL79 open reading frame (ORF) was tagged with the destabilization domain of a highly unstable variant of the human FKBP12 protein (ddFKBP). The ddFKBP domain targets the tagged protein for rapid proteasomal degradation, but the synthetic ligand Shield-1 can stabilize ddFKBP, allowing acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 68 publications
8
81
1
Order By: Relevance
“…We have previously shown that MCMV protein pM79 and its HCMV homologue pUL79 regulate viral late gene expression (13,16). In the present study, we demonstrated that pM92 interacted with pM79 during MCMV infection; likewise, pUL92 could interact with pUL79 during HCMV infection (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We have previously shown that MCMV protein pM79 and its HCMV homologue pUL79 regulate viral late gene expression (13,16). In the present study, we demonstrated that pM92 interacted with pM79 during MCMV infection; likewise, pUL92 could interact with pUL79 during HCMV infection (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Since MCMV M79 and HCMV UL79 play a similar role in late gene expression during infection (13,16), we wanted to determine whether pUL79 also interacted with pUL92, the HCMV homologue of pM92, during infection. To test this, we infected HFF cells with recombinant HCMV expressing N-terminally 3ϫFLAG-tagged pUL79 (ADflagUL79) or wild-type HCMV (ADgfp).…”
Section: Pm92 Is Essential For MCMV Replication In Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50-bp sequences at the 5Ј end of these primers were homologous to the viral DNA sequences immediately upstream or downstream of the amino acid residue 239 of the UL38 ORF: 5Ј-GGAAAATT CCTATGACCTTCGTGGATCGCGACTCGCTGCGAGCCAATTCGTGAA CCACGTCGTGGAATGCCTTC-3Ј and 5Ј-TGCGCCGGGGCGTGAGAAG GCTGAGCCCCGGTGGCCTGGATGTGGGCCAAAAGGACGACGACGA CAAGTAA-3Ј. The cassette was recombined into the UL38 gene carried in pAD-GFP, and the kanamycin sequence was subsequently removed by Flp/FRT recombination as previously described (30). The final clone (pADtrunUL38 ) contained a stop codon along with a small FRT site inserted at the residue 240 of the UL38 ORF.…”
Section: Methodsmentioning
confidence: 99%
“…Due to overlapping adjacent coding regions at the 5= ends of the UL48 and UL103 genes, the FKBP segment (28) was inserted at the 3= end of the target genes. Selective markers (GalK and kanamycin) flanked by FKBP and FRT sequences were PCR amplified from pYD-C630 (provided by Dong Yu, Washington University) (29). The primers for recombineering are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%